Growing the Character of Students Through the Implementation of the Islamic Boarding School Curriculum at the Darul Hijrah Al Aziziyah Kutacane - Syadidul Kahar (Pusdikra-Publishing.com, 2023)
The demand for materialism in the social life of today's society is an indicator that contributes to the formation of mental aridity. This is an encouragement for people to find institutions and figures who can provide spiritual guidance to calm their hearts. So in this case, Islamic educational institutions are an alternative in providing a solution to this anxiety. This research was conducted at the Darul Hijrah Al Aziziyah Kutacane Islamic Boarding School, the research method was carried out using qualitative methods with a phonomenological approach. Based on the results of research that has been carried out, it was found that the Darul Hijrah Al Aziziyah Islamic Boarding School is an institution that manages two curricula, namely the Islamic boarding school curriculum with an emphasis on learning the Yellow Book and the general education curriculum, namely Middle School and High School. Islamic boarding school educational traditions include the yellow book curriculum, the implementation of congregational worship with an emphasis on remembrance of both obligatory worship and sunnah. The emphasis is on dhikr, which in essence does not only mention the name of Allah, but also presents Him in the heart in worship activities. Therefore, dhikr must be carried out using procedures guided by the Islamic boarding school leadership. So in this case, a teacher has a strategic role in the world of information and communication. A teacher has the role of filtering the flow of information entering the student environment, transmitting what is considered useful and discarding what is considered detrimental to them. This is the role of remembrance in shaping the morals and character of students so that students are careless about worship activities and no longer busy themselves with useless negligence.